(untitled) (Eurasian Research Bulletin, 2025)
This article explores the lexical composition of agricultural terminology in the Uzbek language, specifically focusing on the native and borrowed layers. The study identifies the main sources of borrowed terms, including Russian, Arabic, and Persian, and contrasts them with native Uzbek terms that have emerged from traditional practices and folk experience. The article highlights the necessity of enriching and standardizing agricultural vocabulary to reflect both historical heritage and contemporary linguistic needs. By analyzing select examples, the research contributes to the understanding of how lexical stratification shapes the development of specialized terminology in Uzbek.